Transiently Raised IOP Equivalent to That Experienced During Ocular Surgery Causes Moderate Inflammation but does not Affect Retinal Function or Result in Retinal Ganglion Cell Loss in An Animal Model - Jie, Zhang; Rebecca, N. Cole; Peny, Lin; Monica, L. Acosta; Colin, R. Green; Helen, V. Danesh-Meyer (Journal of Ophthalmic Science, 2017)
Purpose: High intraocular pressure (IOP) is known to result in retinal ganglion cell (RGC) loss, both with chronically raised intraocular pressure (such as with glaucoma) and with acute raises in pressure (due to injury or acute angle closure). Because IOP is often raised during ocular surgery, the purpose of this study was to evaluate the effect of transient moderate IOP on retinal function, RGC survival and the expression of Connexin 43 (Cx43) and glial fibrillary acidic protein (GFAP), ubiquitously expressed central nervous system (CNS) proteins that are known to be elevated during the retinal inflammatory response to injury. Materials and Methods: Wistar rats were exposed to transient IOP at 40 mmHg for 5 or 30 minutes, and 60 mmHg for 5 minutes (via cannulation of the anterior chamber with a saline reservoir raised to a height corresponding to the desired IOP), mimicking potential IOP rises during surgery such as DSAEK and some laser procedures (LASIK and femtosecond laser cataract surgery). Separate groups of animals had IOP maintained at 10 mmHg for 5 or 30 minutes as cannulation controls, or 120 mmHg for 60 minutes as positive controls. Changes in the optic nerve and retina were assessed immunohistochemically for GFAP and Cx43 expression. Retinal function was assessed using electroretinography (ERG) recorded at baseline and 14 days after the IOP rise and compared with RGC counts. Results: Results showed that there was a differential GFAP labelling pattern observed in the anterior optic nerve in the 40 mmHg 30 minute and 60 mmHg 5 minute groups 4 hours after manipulation. Gap junction protein Cx43 was minimally up-regulated in the retina in the short-term. There was, however, minimal long-term effect on retinal function and no RGC loss. Conclusions: n conclusion, elevations of IOP that are short in duration such as those occurring during surgical procedures, do not cause significant changes long-term in retinal function or RGC survival. Key Messages: Cx43 and GFAP are known to be elevated during the retinal inflammatory response to injury. No previous study has explored the effect of moderate and relatively short increases in IOP on the initial inflammatory response. We observed a mild glial inflammatory response in the anterior optic nerve, but only a minimal up-regulation of Cx43. However, transient and moderate IOP rises did not induce long term disruption to RGC function or number as measured by electrophysiology and RGC counts, respectively. This is applicable to clinical practice, as it means the IOP elevations that occur during some surgical procedures are unlikely to be causing long term damage in retinal function or RGC survival.
Keywords: DSEK; LASIK; intraocular pressure; inflammation; retinal ganglion cell